Investing in Open Source : The FOSS Contributor Fund - O'Brien, Duane; Grover, Mandy (O'Reilly Media, Inc., 2021)
In January 2019, Indeed, the world's #1 job site, launched a new program that democratizes how the company provides financial support to free and open source software projects. The FOSS Contributor Fund enables Indeed's employees to nominate, vote for, and fund projects. The FOSS Fund is a living blueprint designed to evolve with iteration and to increase meaningful participation in open source. In this report, Indeed's Duane O'Brien and Mandy Grover share each component of this funding blueprint, from establishing eligible projects and voter criteria to securing funding. Learn how to propose, implement, build, and sustain your own FOSS Fund. The authors take you through the process, including: Deciding on the criteria for project funding Understanding who should be eligible to vote Experimenting with budgets and voting cadence Finding a framework that works Deciding when to make changes to your program.